Efecto de la utilización de dos cereales Hordeum vulgare (cebada), Chenopodium quinoa (quinua) y tres fuentes de almidón Manihot esculenta (YUCA), Colocasia esculenta (malanga) E Ipomoea batatas (camote), en la elaboración de cerveza artesanal - Vanegas Romero, Génesis Fernanda (2019)
Currently in Ecuador there is an overproduction of some of the tubers, so it is a matter of concern not to take advantage of the different varieties of those tubers that nature provides, due to the lack of alternative production and industrialization. This research aims to evaluate the effect of two cereals Hordeum vulgare (Barley), Chenopodium quinoa (Quinoa) and sources of starch Manihot esculenta (Yucca), Colocasia esculenta (Taro) and Ipomoea batatas (Sweet potato), in the development of artisan beer. This project seeks to use the cereals and tubers in the elaboration of the craft beer to increase the demand for crops and to take advantage of the raw material harvested in our country. Physicochemical analysis of the beer was carried out as: pH, density, ºGL, acidity, ethanol and methanol. The treatment that was differentiated from the others by its better results was c1a0p2 (quinoa + cassava + 50% cassava starch) which provided better yields according to the study factors. As for the organoleptic results, it obtained excellent acceptance giving a caramel color and a strong smell and flavor characteristic of craft beer and according to the color scale of Lovibond presented the color similary to the beer Bass Pale Ale. Key words: Overproduction, varieties, industrialization, demand, brewery.